Enforcing periodic secondary structures in hybrid peptides: a novel hybrid foldamer containing periodic gamma-turn motifs - Baruah, Pranjal K.; Sreedevi, N. K.; Gonnade, Rajesh G.; Ravindranathan, Sapna; Damodaran, Krishnan; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Journal of Organic Chemistry, 2007)
{This note describes the design, synthesis, and conformational studies of a novel hybrid foldamer that adopts a definite compact, three-dimensional structure determined by a combined effect of the special conformational properties of the foldamer constituents. The striking feature of this de novo designed foldamer is its ability to display periodic gamma-turn conformations stabilized by intramolecular hydrogen bonds. Conformational investigations by single-crystal X-ray studies, solution-state NMR, and ab initio MO theory at the HF/6-31G*
Keywords: ammonia-TPD; benzylation reaction; Ce-Al-MCM-41; Friedel-Crafts alkylation; pyridine-FrIR

Foldamers with unusual structural architecture from spirobi(indane) building blocks - Kendhale, Amol M.; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Chemical Communications, 2008)
This communication demonstrates the utility of inherently rigid building blocks such as 1,1'-spirobi(indane) for generating conformationally ordered synthetic oligomers with structural architectures distinct from those classically observed.

Sequence-specific unusual (1 -> 2)-type helical turns in alpha/beta-hybrid peptides - Prabhakaran, Panchami; Kale, Sangram S.; Puranik, Vedavati G.; Rajamohanan, P. R.; Chetina, Olga; Howard, Judith A. K.; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Journal of the American Chemical Society, 2008)
This article describes novel conformationally ordered (alpha/beta-hybrid peptides consisting of repeating L-proline-anthranilic acid building blocks. These oligomers adopt a compact, right-handed helical architecture determined by the intrinsic conformational preferences of the individual amino acid residues. The striking feature of these oligomers is their ability to display an unusual periodic pseudo beta-turn network of nine-membered hydrogen-bonded rings formed in the forward direction of the sequence by 1–>2 amino acid interactions both in solid-state and in solution. Conformational investigations of several of these oligomers by single-crystal X-ray diffraction, solution-state NMR, and ab initio MO theory suggest that the characteristic steric and dihedral angle restraints exerted by proline are essential for stabilizing the unusual pseudo beta-turn network found in these oligomers. Replacing proline by the conformationally flexible analogue alanine (Ala) or by the conformationally more constrained alpha-amino isobutyric acid (Aib) had an adverse effect on the stabilization of this structural architecture. These findings increase the potential to design novel secondary structure elements profiting from the steric and dihedral angle constraints of the amino acid constituents and help to augment the conformational space available for synthetic oligomer design with diverse backbone structures.

Novel foldamer structural architecture from cofacial aromatic building blocks - Prabhakaran, Panchami; Puranik, Vedavati G.; Chandran, Jima N.; Rajamohanan, Pattuparampil R.; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Chemical Communications, 2009)
This communication demonstrates the utility of peri-substituted 1,8-diphenylnaphthalene as an effective building block for the construction of novel conformationally ordered synthetic oligomers displaying cofacial structural features.

Sterically controlled naphthalene homo-oligoamides with novel structural architectures - Prabhakaran, Panchami; Puranik, Vedavati G.; Chandran, Jima N.; Rajamohanan, P. R.; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2009)
Herein we report novel naphthalene homo-oligoamides, derived from 4-amino-3-methoxy-naphthalene-2-carboxylic acid and 4-amino-1-methoxy-naphthalene-2-carboxylic acid as monomer building blocks, that display an anti-periplanar arrangement of the naphthyl rings, primarily induced by steric interactions between adjacent groups and functionalities.

Expanding the structural repertoire of beta/alpha Ant-Pro (anthranilic acid-proline) oligomers into gamma/alpha 2-Amb-Pro (2-aminomethyl benzoic acid-proline) oligomers - Ramesh, Veera V. E.; Priya, Gowri; Rajamohanan, P. R.; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Tetrahedron, 2012)
In this article, we report a novel class of heterogeneous synthetic oligomers featuring the conformationally constrained amino acid residues - 2-aminomethyl benzoic acid (2-Amb) and proline (Pro) in repeating sequences. Oligomers as large as hexadecamers featuring the conformationally restricted gamma/alpha 2-Amb-Pro motif have been assembled using solution-phase Boc strategy, following multi-step synthetic sequences starting from the commercially available O-toluic acid. EDC-mediated peptide coupling has been found to be optimum for the assembly of the relatively non-polar oligomers, which could be readily purified by the standard column chromatographic purification procedures. This study offers considerable prospects of expanding the structural repertoire of beta/alpha Ant-Pro motif, which has been described earlier to assume right-handed helical architecture displaying robust nine-membered-ring closed network of hydrogen-bonding interactions, into gamma/alpha 2-Amb-Pro motif. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Amino acids; Foldamer; Peptides; Proline; Synthetic oligomers